2020
DOI: 10.1088/1742-6596/1618/4/042035
|View full text |Cite
|
Sign up to set email alerts
|

Wind farm layout optimization with load constraints using surrogate modelling

Abstract: Minimizing the cost of energy of a wind farm is a difficult task, which involves reducing the wake effects while satisfying several constraints. Due to its multidisciplinary nature, this problem is usually solved through numerical optimisers. TOPFARM is one of these tools, and in this paper, we have added to it a constraint on the fatigue loads. The efficiency of the implementation is guaranteed by an extensive use of gradients and load surrogate models. The paper is concluded by showing some case studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…12 A more recent approach integrated generic fatigue loading on structural elements as a design constraint in TOPFARM. 13 Another approach considered fatigue loads on blades and AEP in a multiobjective optimization function. 10 Additionally, previous approaches to layout optimization commonly treat each turbine's coordinates as individual optimization variables.…”
Section: Wind Plant Layout Optimization Load Simulation and Surrogate Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A more recent approach integrated generic fatigue loading on structural elements as a design constraint in TOPFARM. 13 Another approach considered fatigue loads on blades and AEP in a multiobjective optimization function. 10 Additionally, previous approaches to layout optimization commonly treat each turbine's coordinates as individual optimization variables.…”
Section: Wind Plant Layout Optimization Load Simulation and Surrogate Modelingmentioning
confidence: 99%
“…Layout optimization based on structural component damage equivalent loading constraints were integrated by Riva et al into the MDAO-based TOPFARM. 13 The integration of blade loads into layout optimization was explored by Stanley et al using CCBlade; 48 they found that AEP is similar when optimizing a 10-turbine array with and without total damage constraints.…”
Section: Wind Plant Layout Optimization Load Simulation and Surrogate Modelingmentioning
confidence: 99%
“…Neural network models have been used to build efficient surrogate models based on measured operational data or high-fidelity simulation data. These surrogate models are capable of estimating wake-induced effects on wind turbine power [1,2,3], loads [4,5], damage and failures [6]. These surrogate models, among other applications, enable efficient optimization of wind farm layout and control strategy [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Of those papers, only three consider the entire plant [8][9][10], while the other papers consider only a single upstream turbine [11][12][13]. There is a similar dearth of research literature for loads-aware plant-layout optimization: only two papers have considered loads during plant-layout optimization [14,15]. Of those two papers, one presented only a single, simple optimization layout [14] and the other considered the fatigue loads for only one load channel: the blade-root edgewise moment [15].…”
Section: Introductionmentioning
confidence: 99%
“…There is a similar dearth of research literature for loads-aware plant-layout optimization: only two papers have considered loads during plant-layout optimization [14,15]. Of those two papers, one presented only a single, simple optimization layout [14] and the other considered the fatigue loads for only one load channel: the blade-root edgewise moment [15]. The lack of robust publications in this area makes it difficult to draw concrete conclusions about whether the potential increase in plant production is negated by a correlated increase of wind turbine loads.…”
Section: Introductionmentioning
confidence: 99%